Minat Siswa Dalam Kurikulum Muatan Lokal - Sumiyati -- (Jurnal Pendidikan dan Kebudayaan, 2010)
This research is a survey research, which aim to know what is the relationship between motivation and lerning condition with learning interest of student local content at junior high school in West Jakarta. There are three research hypothesis, first is there is a positive relation between motivation with learning interest of student local content, second is there is a positive relation between learning condition with learning interest of student local content, and third is there is a positive relation between motivation and learning condition with learning interest of student local content. This subject research is student of junior high school in West Jakarta enlisted in the year lesson 2009/2010 with the sample amount 55 people. Technique of data collecting performed is use questionnaire. Based of the result analysis data and solution obtained that Fhit is more than Ftable or 4,66 more than 3,18. It means that there is a positive relation between motivation and learning condition with learning interest of student local content.Â ABSTRAKÂ Penelitian survei ini bertujuan untuk mengetahui apakah terdapat hubungan antara motivasi dan kondisi belajar dengan minat belajar muatan lokal siswa SMP di Jakarta Timur. Hipotesis penelitian ini ada tiga yaitu, pertama terdapat hubungan positif antara motivasi dengan minat belajar muatan lokal siswa, kedua terdapat hubungan positif antara kondisi belajar dengan minat belajar muatan lokal siswa, dan ketiga terdapat hubungan positif antara motivasi dan kondisi belajar dengan minat belajar muatan lokal siswa. Subjek penelitian ini adalah siswa SMP di Jakarta Timur yang terdaftar dalam tahun ajaran 2009/2010, dengan jumlah sampel 55 orang. Teknik pengumpulan data yang dilakukan adalah dengan menggunakan angket. Dari hasil analisis data dan pembahasan diperoleh bahwa F hitung > dari F tabel atau 4,66 lebih besar dari 3,18 artinya terdapat hubungan positif antara motivasi belajar dan kondisi belajar dengan minat belajar muatan lokal siswa.Â